The importance of conservation services on paved roads (Research, Society and Development, 2019)
The purpose of this article is to address the main functions, characteristics, and, finally, methodologies employed in road conservation services at Federal Highways, specifically on Highway BR-116 between km 207.1 and Km.306.5. The peculiarities related to conservation services will be analyzed in a comprehensive and comprehensible way, in the sense that it is possible to minimize the pathologies caused by poor road conservation, as well as avoid expenses that have always burdened the public coffers. Once a highway has been deployed, so that it can have a useful life, that is, in conditions of trafficability and safety for its users, it will require multidisciplinary operations, with resources properly allocated for that purpose, equipment and skilled labor that will play paper fundamental in the mitigation of pathologies arising from the highway's own time of use, as well as from the weather.